Proceedings of the Twelfth Conference on Applied Linguistics (CONAPLIN 2019) 2020
DOI: 10.2991/assehr.k.200406.008
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Condolences Speech Act by Indonesian Adolescents

Abstract: This study aims to identify strategies in condolence expressions and explain the effect of power and distance on the choice of condolences strategies used by 20 Indonesian adolescents at the age of 11 to 19 years old. The study was employed by using a qualitative descriptive method. In the form of discourse completion task (DCT), the data were analyzed using Elwood's (2004) classification of condolences strategies and Brown and Levinson's (1987) theory of politeness. Based on 20 condolence expressions for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 2 publications
1
11
2
Order By: Relevance
“…By contrast, the current study revealed that the main condolence strategy used by native English speakers was expressing good wishes for the deceased. The present study's findings are also not totally in line with Nurlianingsih and Imperiani (2020). To be more specific, although seeking absolution from God was among the observed condolence strategies in this study, it was not ranked the first in any of the groups.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…By contrast, the current study revealed that the main condolence strategy used by native English speakers was expressing good wishes for the deceased. The present study's findings are also not totally in line with Nurlianingsih and Imperiani (2020). To be more specific, although seeking absolution from God was among the observed condolence strategies in this study, it was not ranked the first in any of the groups.…”
Section: Discussioncontrasting
confidence: 96%
“…To be more specific, although seeking absolution from God was among the observed condolence strategies in this study, it was not ranked the first in any of the groups. This is however in contrast with Nurlianingsih and Imperiani (2020) who reported that Indonesian speakers mostly use this condolence strategy, seeking absolution from God, in their talks.…”
Section: Discussioncontrasting
confidence: 67%
“…In expressing condolences, speakers are required to be careful because of the sensitive nature of death; the language used in conveying condolence messages needs to be carefully chosen and offered in appropriate emotions and tone based on the culture of the deceased. In the same view, Nurlianingsih and Imperian (2019) asserted that the language used in normal conversation is different from the one used in such emotional situations like death. This makes giving condolences to be a challenging issue to many people.…”
Section: Introductionmentioning
confidence: 99%
“…This calls for more studies to be conducted. Most of the previous studies have investigated the speech of giving condolences in other languages than Kiswahili (Nurlianingsih and Imperian, 2019;Al-Shboul and Maros, 2013;Moghaddam, 2012. Therefore, this study examined condolence strategies used in response to the death of Dr. John Joseph Magufuli using Kiswahili Language on Facebook.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed three strategies for expressing condolence such as acknowledgement of sympathy, question of concern, and inquiry for information. Another research done by (Nurlianingsih & Ayu Imperiani, 2020) shows that the responses from the Facebook users asking the absolution from God. The research about obituary also can be a material teach in the character building (A Sabardila, A Sunanda, Y Sulistyono, D R Pratiwi, 2020).…”
Section: Introductionmentioning
confidence: 99%